100 classic hikes New England 2023 : Maine, New Hampshire, Vermont, Massachusetts, Connecticut, Rhode Island - Romano, Jeffrey (Mountaineers Books, 2023)
"Author Jeffrey Romano, a New England native, covers the best trails across six states, including hikes on Vermont's famous Long Trail, the challenging rocky peaks of New Hampshire's White Mountains, in the forests of Connecticut and the many conservation areas of Massachusetts, and along the picturesque coasts of Maine and Rhode Island. Romano provides options for both shortening or extending many hikes so everyone can find the route that matches their skill and energy level-and, of course, includes distances and times for each route, as well as difficulty rating, elevation gain, permitting information, and more. Whether they are looking for an easy jaunt, a longer day hike, or a multi-day backpacking experience, hikers will find it all in 100 Classic Hikes New England, 2nd Edition"--